Antimicrobial Activity of Methanol Crude Extract and Alkaloid Fraction of Carica Papaya Leaves on Methicillin Resistant Staphylococcus aureus - Enwa Felix Oghenemaro *, Mokogwu Azukaego Thomas Hughs , Avwunudiogba John Avweruosuo , Monye Samuel Chiweike (Sokoto Journal of Medical Laboratory Science)
Therapeutic plant parts since time immemorial have been used by man for the treatment of numerous diseases. For this reason, this study was carried out to determine the antibacterial activity of the crude extract as well as the alkaloid fraction of carica papaya leaves against Methicillin Resistant Staphylococcus aureus (MRSA). Phytochemical screening was done following standard procedures and the minimum inhibitory concentration (MIC) and susceptibility of the samples of the organism (MRSA) to various concentration of the methanol (crude) extract and the alkaloid fraction of Carica papaya was determined using the agar well diffusion technique. Phytochemical screening of the leaves reveals the presence of tannins, alkaloids, proteins, reducing sugar and phenols. The leaf extract and Alkaloid fraction demonstrated mild to moderate antimicrobial activity against the microorganism at different concentrations with high zones of inhibition 11±0.000mm, 7±1.414mm, 4±0.000mm, 4±0.000mm respectively for the alkaloid fraction although lower concentrations of the extracts and fraction showed no observable activity. Generally, the samples of MRSA used appeared to be more susceptible to the alkaloid fraction than the crude extract of the Carica papaya. The alkaloid fraction of the plant’s leaves had comparable and even higher activity to that of Oxacillin used. The finding from this study may be of interest and the need for further investigation in terms of toxicological and antimicrobial studies with the sole purpose of using plant in novel drug design and development.